1965
DOI: 10.1128/jb.89.4.988-992.1965
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance of Staphylococci II. Joint Elimination and Joint Transduction of the Determinants of Penicillinase Production and Resistance to Macrolide Antibiotics

Abstract: Drug resistance of staphylococci. II. Joint elimination and joint transduction of the determinants of penicillinase production and resistance to macrolide antibiotics. J. Bacteriol. 89:988-992. 1965.-Strains of Staphylococcus aureus, which show high resistance to macrolide antibiotics (erythromycin, oleandomycin, leucomycin, and spiramycin) and the capacity to produce penicillinase, have been isolated from clinical sources. The determinants of penicillinas] production (PCase+) and resistance to macrolide antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

1969
1969
1982
1982

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…According to the curing experiment and the genetic analysis, it was concluded that the locus for resistance to macrolide (Mac) antibiotics [13] and that for PC-resistance (penicillinase formation) [7,15,18] exist on a plasmid, indicating the existence of Table 5. Relative location of the loci controllingresistance to CM, TC and to SM either a (Mac.…”
Section: Discussionmentioning
confidence: 99%
“…According to the curing experiment and the genetic analysis, it was concluded that the locus for resistance to macrolide (Mac) antibiotics [13] and that for PC-resistance (penicillinase formation) [7,15,18] exist on a plasmid, indicating the existence of Table 5. Relative location of the loci controllingresistance to CM, TC and to SM either a (Mac.…”
Section: Discussionmentioning
confidence: 99%
“…Many papers have described the unstable resistance in staphylococci including the resistance to macrolide antibiotics [11,13,16], TC [1,8,10], PC [2,3,7,9,13,15], kanamycin [4] and chloramphenicol [4,9]. The first results of irreversible elimination of resistance to macrolide (Mac) antibiotics led us to the conclusion that the determinant responsible for Mac-resistance in staphylococci is located extrachromosomaly, probably being on a plasmid [11,16].…”
Section: Discussionmentioning
confidence: 99%
“…The first results of irreversible elimination of resistance to macrolide (Mac) antibiotics led us to the conclusion that the determinant responsible for Mac-resistance in staphylococci is located extrachromosomaly, probably being on a plasmid [11,16]. According to transduction analysis and genetic investigation, it was concluded that there were probably two plasmids; one carrying a PC-resistance determinant and another harboring both PC-and Mac-re-sistance determinants [7,[13][14][15][16]. Thereafter, many papers presented further proof that the genetic determinants for drugresistance in staphylococci are located on plasmid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations